Painful sex (dyspareunia) in women: prevalence and associated factors in a British population probability survey. (25th January 2017) - Mitchell, KR; Geary, R; Graham, CA; Datta, J; Wellings, K; Sonnenberg, P; Field, N; Nunns, D; Bancroft, J; Jones, KG; Johnson, AM; Mercer, CH
Abstract : Objective: To estimate the prevalence of painful sex among women in Britain, and to explore associated sexual, relationship and health factors that should be considered in assessment. Design: Multi‐stage, clustered and stratified population probability sample survey, using computer‐assisted self‐interview. Sample frame was the British Postcode Address File. Setting: Participants interviewed at home between 2010 and 2012. Sample: A total of 15 162 adults aged 16–74 years (8869 women). Data reported from 6669 sexually active women. Methods: Age‐adjusted logistic regressions to examine associations between painful sex and indicators of sexual, relational, mental and physical health. Main outcome measure: Physical pain as a result of sex for ≥3 months in the past year, plus measures of symptom severity. Results: Painful sex was reported by 7.5% (95% CI 6.7–8.3) of sexually active women, of whom one‐quarter experienced symptoms very often or always, for ≥6 months, and causing distress. Reporting painful sex was strongly associated with other sexual function problems, notably vaginal dryness (age adjusted odds ratio 7.9; 6.17–10.12), anxiety about sex (6.34; 4.76–8.46) and lacking enjoyment in sex (6.12; 4.81–7.79). It was associated with sexual relationship factors [such as not sharing same level of interest in sex (2.56; 1.97–3.33)], as well as with adverse experiences such as non‐volitional sex (2.17; 1.68–2.80). Associations were also found with measures of psychological and physical health, including depressive symptoms (1.68; 1.28–2.21). Conclusion: Painful sex is reported by a sizeable minority of women in Britain. Health professionals should be supported to undertake holistic assessment and treatment which takes account of the sexual, relationship and health context of symptoms. Tweetable abstract: Painful sex—reported by 7.5% of women in Britain—is linked to poorer sexual, physical, relational and mental health. Tweetable abstract: Painful sex–reported by 7.5% of women in Britain–is linked to poorer sexual, physical, relational and mental health. This article includes Author Insights, a video abstract available athttps://vimeo.com/rcog/authorinsights14518 .